Relevance of Symbol Systems Theory to Instructional Media for the Enhancement of Social Studies Learning Outcome - Atubi, Onamrewho Favour (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2023)
The application of instructional media resources for Social Studies instructions can offer a clear departure from traditional mode of teaching resources, methods and strategies. Hence this study looked at how the symbol system theory can be used as a basis for the application of instructional media to enhance social studies students’ learning outcome. The research design for the study was quasi experimental. Random sampling technique was applied in selecting 30 Junior Secondary school students from a population of 150 in Covenant school Eku in Delta State of Nigeria. Researchers developed test titled “Instructional Media Performance Test (IMPT)”, was the instrument of data collection. The reliability of the instrument using Cronbach alpha was 0.79, t-test was used to test the two hypotheses of the study. The findings revealed that there was no significant difference in the pre-tests given to the students in both treatment and control groups as calculated value of 4.04 was lesser than table value of 5.09; also there is a positive and significant influence of instructional media (television) on the learning outcome of Junior Secondary Students in social studies as calculated value of 5.68 is higher than table value of 4.09. To this end, the study suggested that social studies teachers should incorporate instructional media (television) where necessary to achieve optimum learning objective, goals and heighten the learning outcome of Junior Secondary School students in social studies.